Primary ciliary dyskinesia in Volendam: Diagnostic and phenotypic features in patients with a CCDC114 mutation. Issue 1 (27th March 2022) - Kos, Renate; Israëls, Joël; van Gogh, Christine D. L.; Altenburg, Josje; Diepenhorst, Sandra; Paff, Tamara; Boon, Elles M. J.; Micha, Dimitra; Pals, Gerard; Neerincx, Anne H.; Maitland‐van der Zee, Anke H.; Haarman, Eric G.; et al.
Abstract: Primary ciliary dyskinesia (PCD) is a heterogeneous disease, with impaired mucociliary clearance causing respiratory tract infections. A founding CCDC114 mutation has led to a relatively homogeneous and large Dutch PCD population in Volendam. Our aim was to describe their phenotype. Therefore, all Volendam PCD patients seen at the Amsterdam UMC were included in this study. Data were collected on lung function, microbiology, radiology, and ear‐nose‐throat (ENT) symptoms. A mixed effects model estimated lung function decline in %point per year (95% confidence interval [CI]). Thirty‐three (60%) out of approximately 56 Volendam PCD patients were treated at our center and included in this study. Only 30% of patients had situs inversus. FEV1 declined in children (−1.43%/year, CI: −1.80/−1.05), but not in adults (0.01%/year, CI: −0.36/0.38). Pseudomonas aeruginosa was cultured in 21% of children and 60% of adults, respectively. Patients who have been infected at some point with P. aeruginosa had a steeper decline in FEV1 as compared to patients that have never been infected. Neonatal symptoms (79%) and ENT problems (94%) were common; fertility issues however, were not (11%) common. Compared to other PCD cohorts, the Volendam/CCDC114 patients have a moderately severe phenotype with lung function decline predominantly occurring in childhood.